Hexagonal Circular 3-Webs with Reducible Polar Curves of Degree Three - Agafonov, Sergey I. (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
The paper reports the progress with the classical problem, posed by Blaschke and Bol in 1938. We present new examples and new classifications of natural classes of hexagonal circular 3-webs. The main results are the classification of hexagonal circular 3-webs with reducible polar curves of degree 3 and the description of hexagonal circular 3-webs admitting a one-parameter Möbius symmetry.